SUN-740 Low-Dose Dihydrotestosterone Lowers Lipogenic Master Regulator in Liver and Adipose Tissue from Female Mice - Seidu, Tina (J Endocr Soc, 2020)
Hyperandrogenemia (HA) and insulin resistance (IR) are hallmarks of polycystic ovary syndrome (PCOS), a common endocrine disorder that affects 1 in 10 women. These hallmarks are also integral elements of non-alcoholic liver disease (NALFD), a disorder that is common in women with PCOS. Administering low dose dihydrotestosterone (DHT) induced a lean female mouse model with a PCOS-like phenotype, displaying IR and NAFLD. The molecular mechanism of HA-induced NAFLD has not been determined. We hypothesized that low dose DHT would interrupt hepatic lipid metabolism leading to NAFLD. To investigate the role of androgens on the master regulator of lipogenesis, sterol regulatory element-binding protein 1 (SREBP1), we extracted white adipose tissue (WAT), liver, and skeletal muscle from wild-type, control and low dose DHT female mice; and performed Western blot and real-time quantitative PCR (qRT-PCR) analysis of lipogenic intermediates of the tissue homogenates. Low-dose DHT lowered the active form of cytosolic SREBP1 in the liver and WAT compared to controls. Additionally, low dose DHT lowered inactive SREBP1 in the liver. However, the condition did not alter the levels of the active and inactive forms of SREBP2 in the liver and WAT, though the active form was lowered in skeletal muscle. Further, p-ACC levels were unaltered in liver and WAT. FAS levels were unchanged in WAT and skeletal muscle. Taken together, our findings support the hypothesis that cytosolic SREBP1 decreased due to its translocation to the nucleus, where it regulates lipogenic protein levels. We speculate that low-dose DHT promotes the translocation of SREBP1 from the cytosol to the nucleus to influence lipogenic gene expression leading to increased lipogenesis contributing to NAFLD.